2015
DOI: 10.3233/com-150040
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic density, immunity and randomness

Abstract: Abstract. In 2012, inspired by developments in group theory and complexity, Jockusch and Schupp introduced generic computability, capturing the idea that an algorithm might work correctly except for a vanishing fraction of cases. However, we observe that their definition of a negligible set is not computably invariant (and thus not well-defined on the 1-degrees), resulting in some failures of intuition and a break with standard expectations in computability theory.To strengthen their approach, we introduce a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…(g −1 (A)) ≥ 1 − 1 n . Since this occurs for infinitely many n, we conclude that g samples A with upper density 1, and thus (by Lemma 4.2 of [1]) that A has absolute upper density 1. Take h(n) = n 2 (or, indeed, any computable superlinear function), and let f ≤ T A be as above.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…(g −1 (A)) ≥ 1 − 1 n . Since this occurs for infinitely many n, we conclude that g samples A with upper density 1, and thus (by Lemma 4.2 of [1]) that A has absolute upper density 1. Take h(n) = n 2 (or, indeed, any computable superlinear function), and let f ≤ T A be as above.…”
mentioning
confidence: 70%
“…In a previous paper [1], the author suggested that we instead consider sets to be thin if no computable process can sample the set at positive density infinitely often (i.e., with positive upper density); we say such a set has intrinsic density 0. More precisely: We can weaken this slightly, instead asking only that no sampling succeeds with positive density in the limit (i.e., with positive lower density).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We will show in the next section that, as one might expect, the converse fails. The development of the theory of notions of robust information coding and related concepts have led to interactions with computability theory (as in Jockusch and Schupp [13]; Downey, Jockusch, and Schupp [4]; Downey, Jockusch, Mc-Nicholl, and Schupp [5]; and Hirschfeldt, Jockusch, McNicholl, and Schupp [10]), reverse mathematics (as in Dzhafarov and Igusa [7] and Hirschfeldt and Jockusch [9]), and algorithmic randomness (as in Astor [1]).…”
Section: Introductionmentioning
confidence: 99%